Analogies of Deconstruction: J. Hillis Miller’s Uncanny Pedagogy - Csató, Péter (AMERICANA E-journal of American Studies in Hungary, 2022)
The article focuses on theoretical texts from J. Hillis Miller’s “middle period,” written between the mid-1970s and the late 1980s, at the heyday of the Yale school of deconstruction. Besides his multifaceted oeuvre, Miller’s fame arguably rests mainly on the theoretical and critical work he produced as a “Yale Critic,” alongside Paul de Man, Geoffrey Hartman, Harold Bloom, with Jacques Derrida. The study analyses two of Miller’s most influential (and controversial) texts in more detail: “Stevens’ Rock and Criticism as Cure, II” (1976) and “On Edge: The Crossways of Contemporary Criticism” (1979). The choice of texts has been motivated by the fact that they contain some of the most eloquent and lucid explications, via vividly imaginative analogies, of how deconstruction as a “method” works. Analyzing Miller’s illuminating analogies of criticism, the paper demonstrates that his lucidity is bound to get in the way of the deconstructive enterprise he is supposed to promote, producing inconsistencies and anomalous arguments in his texts. I will argue, however, that the anomalies stem from the fact that Miller’s pedagogical urge to share knowledge is stronger than his commitment to the actual practice of deconstruction. He must ground his explications in a coherent narrative to make them communicable, while at the same time he has to defend the deconstructive thesis that positing such grounding principles is constantly undermined by treacherous workings of language.